2021
DOI: 10.1262/jrd.2020-141
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the RhoA/Rho associated kinase pathway and leptin in primary uterine inertia in the dog

Abstract: The underlying functional and molecular changes in canine primary uterine inertia (PUI) are still not clarified. Leptin (Lep) and obesity negatively affect uterine contractility in women, partly mediated by the RhoA/Rho kinase pathway, affecting myometrial calcium sensitization. We hypothesized that increased uterine Lep/Lep receptor (LepR) or decreased RhoA/Rho kinase expression contributes to PUI in dogs, independent of obesity. Dogs presented for dystocia were grouped into PUI (n = 11) or obstructive dysto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 51 publications
2
13
0
Order By: Relevance
“…Furthermore, prolonged intracervical pressure, resulting in increased hypophyseal OXT release, could contribute to this desensitization. A decreased mRNA expression of other contractile and contractility associated proteins in IP sections of OD compared to PUI bitches has also been shown in our previous reports [ 16 , 17 ], corroborating the current findings and the proposed role of prolonged labor contractions on the uterus. Indeed, all OD bitches included in our study still showed strong straining as a response to digital vaginal feathering and spontaneous abdominal and/or uterine contractions, indicating that these bitches did not reach myometrial fatigue, causing secondary UI.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Furthermore, prolonged intracervical pressure, resulting in increased hypophyseal OXT release, could contribute to this desensitization. A decreased mRNA expression of other contractile and contractility associated proteins in IP sections of OD compared to PUI bitches has also been shown in our previous reports [ 16 , 17 ], corroborating the current findings and the proposed role of prolonged labor contractions on the uterus. Indeed, all OD bitches included in our study still showed strong straining as a response to digital vaginal feathering and spontaneous abdominal and/or uterine contractions, indicating that these bitches did not reach myometrial fatigue, causing secondary UI.…”
Section: Discussionsupporting
confidence: 92%
“…Despite the frequent occurrence of PUI in dogs and its severe consequences for maternal and offspring survival, the exact etiology is still unknown. Up to now, only few studies have investigated its pathophysiology from a molecular biology approach looking directly at the level of the uterus [ 16 , 17 , 32 , 45 , 46 ]. As both oxytocin and progesterone are crucial hormones during parturition, we hypothesized and identified altered expression of the respective receptors as potential causes for PUI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations